Artificial Neural Networks in Pattern Recognition 10th IAPR TC3 Workshop, ANNPR 2022, Dubai, United Arab Emirates, November 24-26, 2022, Proceedings - El Gayar, Neamat; Trentin, Edmondo; Ravanelli, Mirco; Abbas, Hazem (Cham : Springer International Publishing : Imprint: Springer, 2023)
This book constitutes the refereed proceedings of the 10th IAPR TC3 International Workshop on Artificial Neural Networks in Pattern Recognition, ANNPR 2022, held in Dubai, UAE, in November 2022. The 16 revised full papers presented were carefully reviewed and selected from 24 submissions. The conference presents papers on subject such as pattern recognition and machine learning based on artificial neural networks. .
Transformer-Encoder generated context-aware embeddings for spell correction -- Graph Augmentation for Neural Networks Using Matching-Graphs -- Wavelet Scattering Transform Depth Benefit, An Application for Speaker Identification -- Assessment of Pharmaceutical Patent Novelty using Siamese Neural Network -- A Review of Capsule Networks in Medical Image Analysis -- Multi-stage Bias Mitigation for Individual Fairness in Algorithmic Decisions -- Introducing an Atypical Loss: A Perceptual Metric Learning for Image Pairing -- A Study on the Autonomous Detection of Impact Craters -- Minimizing Cross Intersections in Graph Drawing via Linear Splines -- Sequence-to-Sequence CNN-BiLSTM Based Glottal Closure Instant Detection from Raw Speech -- Do Minimal Complexity Least Squares Support Vector Machines Work? -- A Novel Representation of Graphical Patterns for Graph Convolution Networks -- Mono vs Multilingual BERT for Hate Speech Detection and Text Classification: A Case Study in Marathi Utilization of Vision Transformer for Classification and Ranking of Video Distortions -- White Blood Cell Classification of Porcine Blood Smear Images -- Medical Deepfake Detection using 3-Dimensional Neural Learning.
Keywords: Artificial intelligence; Education -- Data processing; Data mining; Application software; Social sciences -- Data processing; Computer vision; Artificial Intelligence; Computers and Education; Data Mining and Knowledge Discovery; Computer and Information Systems Applications; Computer Application in Social and Behavioral Sciences; Computer Vision